Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.7704/kjhugr.2011.11.3.170
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of Astaxanthin and α-tocopherol in Esophageal Cancer Cell Lines

Abstract: Background/Aims: Astaxanthin (AX) has been attributed with potential for protecting the organism against different types of cancer due to its anti-oxidant activity. Also several in vivo and in vitro studies suggest certain naturally occurring vitamin E (i.e. α-tocopherol) as promising anticancer agents. We assessed the effect of AX and α-tocopherol (AT) respectively and their combination on human esophageal cancer cell lines to investigate the mechanism of anticancer effect and their therapeutic potential. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…They reduced not only the expression of p-Akt and cyclin D1, but also exhibited a higher caspase-3 expression than XNT’s treatment alone in both esophageal cancer cells. On the other hand, previous studies indicated that combined astaxanthine and α-tocopherol did not exhibit any cooperative apoptosis, where they increased the expression of p-Akt and maintained caspase-3 levels compared to control [ 91 ]. In fact, astaxanthine or α-tocopherol treatment alone was effective against TE-1 and TE-4 esophageal cancer cells, but not their combination [ 91 ].…”
Section: Xnt In Cancer Treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…They reduced not only the expression of p-Akt and cyclin D1, but also exhibited a higher caspase-3 expression than XNT’s treatment alone in both esophageal cancer cells. On the other hand, previous studies indicated that combined astaxanthine and α-tocopherol did not exhibit any cooperative apoptosis, where they increased the expression of p-Akt and maintained caspase-3 levels compared to control [ 91 ]. In fact, astaxanthine or α-tocopherol treatment alone was effective against TE-1 and TE-4 esophageal cancer cells, but not their combination [ 91 ].…”
Section: Xnt In Cancer Treatmentmentioning
confidence: 94%
“…On the other hand, previous studies indicated that combined astaxanthine and α-tocopherol did not exhibit any cooperative apoptosis, where they increased the expression of p-Akt and maintained caspase-3 levels compared to control [ 91 ]. In fact, astaxanthine or α-tocopherol treatment alone was effective against TE-1 and TE-4 esophageal cancer cells, but not their combination [ 91 ]. Thus, we postulate that the addition of XNT to astaxanthine and α-tocopherol may stimulate their antiproliferative properties giving synergistic effects.…”
Section: Xnt In Cancer Treatmentmentioning
confidence: 94%
“…Moreover, an antioxidant and antiproliferative effect on a human bladder cancer cell line (T24) has been reported after 48 hours, depending on chitosan concentration [ 25 ]. The effect of one of the compounds derived from chitin, astaxanthin, on a human esophagus cancer cell line (TE-4) over 24, 48, and 72 hours was investigated, and dose-dependent inhibition was observed [ 26 ]. Furthermore, astaxanthin derived from the green alga Haematococcus pluvialis exerted an inhibitory effect on a large intestine cancer cell line (HCT-116) via apoptosis induction [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…showed that AXT has the potential to act as a therapeutic agent in atherosclerotic cardiovascular disease due to its potent antioxidant and anti-inflammatory properties [28]. Compared with inorganic therapeutic agents, AXT can provide a wide variety of benefits as a natural [3234], non-toxic [35, 36] material that has a high molar extinction coefficient [37, 38]. Additionally, the United States Food and Drug Administration has approved AXT for use as a dietary supplement [31].…”
Section: Introductionmentioning
confidence: 99%